Odpowiedź:
zad 1
x(x - 2)(x - 3) = 0
x = 0 ∨ x - 2 = 0 ∨ x - 3 = 0
x = 0 ∨ x = 2 ∨ x = 3
Odp: b
zad 2
x(x² + 1)(x - 1)(x + 1) = 0
ponieważ x² + 1 > 0 dla x ∈ R , więc :
x(x - 1)(x + 1) = 0
x = 0 ∨ x - 1 = 0 ∨ x + 1 = 0
x = 0 ∨ x = 1 ∨ x = - 1
suma pierwiastków równania = 0 + 1 - 1 = 0
Odp: c
tgα = 3/4
sin²α/cos²α = 9/16
16sin²α = 9cos²α
16sin²α = 9(1 - sin²α)
16sin²α = 9 - 9sin²α
16sin²α + 9sin²α = 9
25sin²α = 9
sin²α = 9/25
sinα = √(9/25) = 3/5
cos²α = 1 -sin²α = 1 - 9/25 = 25/25 - 9/25 = 16/25
cosα = √(16/25 = 4/5
5sin2α - 2cosα = 5 * 2sinαcosα - 2 * 4/5 = 5 * 2 * 3/5 * 4/5 - 8/5 =
= 120/25 - 8/5 = 24/5 - 8/5 = 16/5 = 3 1/5
Nie ma takiej odpowiedzi w wykazie